Management of Generalised Anxiety Disorder through Individualised Homoeopathic Medicine: A Case Study - Khadim, Azizul Islam (Homœopathic Links, 2023)
Background Anxiety disorder is the most common psychological problem in this modern era. It is characterised by cognitive, somatic, emotional and behavioural components. Anxiety can affect the quality of life of an individual and can interfere with a person's career, academics, job, family and social life. Owing to the prolonged side effects from conventional medication, patients turn towards homoeopathy for safe, gentle and effective treatment.Method A 23-year-old male diagnosed with generalised anxiety disorder (GAD) came to outpatient department after having consulted other physicians without benefit. The patient received individualised homoeopathic medicine. Outcome was measured using the GAD-7 every 3 months.Results At the start of the treatment, the patient's GAD-7 score was 16 which reflected severe anxiety. After 9 months, it was reduced to 2.Conclusion This case demonstrates the utility of individualised homoeopathic treatment in improving GAD within 9 months of treatment. Nevertheless, large sample randomised controlled study would be required to support this single case observation.
Keywords: GAD; GAD-7 Score; individualised medicine; homoeopathy; Arsenicum album